Diversity and functions of protein glycosylation in insects. (April 2017) - Walski, Tomasz; De Schutter, Kristof; Van Damme, Els J.M.; Smagghe, Guy
Abstract: The majority of proteins is modified with carbohydrate structures. This modification, called glycosylation, was shown to be crucial for protein folding, stability and subcellular location, as well as protein-protein interactions, recognition and signaling. Protein glycosylation is involved in multiple physiological processes, including embryonic development, growth, circadian rhythms, cell attachment as well as maintenance of organ structure, immunity and fertility. Although the general principles of glycosylation are similar among eukaryotic organisms, insects synthesize a distinct repertoire of glycan structures compared to plants and vertebrates. Consequently, a number of unique insect glycans mediate functions specific to this class of invertebrates. For instance, the core α1, 3-fucosylation of N- glycans is absent in vertebrates, while in insects this modification is crucial for the development of wings and the nervous system. At present, most of the data on insect glycobiology comes from research in Drosophila. Yet, progressively more information on the glycan structures and the importance of glycosylation in other insects like beetles, caterpillars, aphids and bees is becoming available. This review gives a summary of the current knowledge and recent progress related to glycan diversity and function(s) of protein glycosylation in insects. We focus on N- and O- glycosylation, their synthesis, physiological role(s), as well as the molecular and biochemical basis of these processes. Graphical abstract: Highlights: Thousands of insect proteins are glycosylated. Insects produce a large diversity of N - and O -linked glycans. N- glycans are required for protein quality control, nervous system function and immune response. Major roles for O -glycans include tissue development, adhesion, signaling and circadian clock regulation.